EXPLORATION OF FOREST CHANGE TRENDS IN BIOSPHERE RESERVES, TABASCO, FROM SPACE - Rullán Silva, Cristóbal Daniel; Olthoff, Adriana Ema (Kuxulkab’, 2024)
This work analysed spectral data on forest cover change to explore forest dynamics over 23 years in two Natural Protected Areas with Biosphere Reserve status in Tabasco. These data were obtained free of charge from Global Forest Watch, and accessed through the Google Earth Engine platform. Specifically, the Hansen Global Forest Change dataset on areas of both reserves was used for subsequent analysis at the regional level in a geographic information system. The results provide information on forest changes; some are verified as real, but most have inconsistencies because they come from a planetary scale. Hansen Global Forest Change is an important application as a research and operational resource for deriving and updating information on forest change at local scales for monitoring deforestation, regeneration and reforestation.